An exploratory study of Malaysian tax practitioner's perception on the practice of aggressive tax avoidance - Nur Fikhriah binti Takril (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2012)
Malaysian tax research has put little attention on the tax morale of Malaysian tax environment. Therefore, the objective of this study is to explore the perception of Malaysian tax practitioners in giving tax advice to tax clients whether to promote aggressive tax avoidance or to promote tax compliance. It is accordance to the implementation of SAS which had given taxpayers freedom to declare their income and compute their own tax liability. This self-determination in tax assessment had given them the opportunity to manipulate the tax account which resulted to lower or minimum tax paid. Aggressive tax avoidance is a non-compliance behavior by exploiting tax law ambiguity, playing with accounting figures and transactions to reduce tax. Moreover, the SAS had increases the demand of tax practitioners services as most taxpayers especially from the corporate sector feel incompetence and unqualified to file their own tax affairs appropriately. A survey approach is used to obtain information from tax practitioners practicing in public accounting firms in urban towns. Tax practitioners who perceived leniently on the practice of aggressive tax avoidance signify a likelihood of aggressive tax avoidance participation. The finding of this study shows that Malaysian tax practitioners perceived aggressive tax avoidance as unethical behavior. The aggressive tax avoidance practice is contributed by the tax clients' incomplete documentation and competitive tax environment. However, the results also indicate that tax practitioners are at the state of dilemma whether to satisfy their tax clients request to minimize tax or to the society demand for a fair tax share. The results also indicate that there is a need for collaborative and collective effort from various parties such as taxpayers, tax practitioners and tax authority to shape and sustain a good environment of tax practices.